Convergence of an Inertial Shadow Douglas-Rachford Splitting Algorithm for Monotone Inclusions. (26th October 2021) - Fan, Jingjing; Qin, Xiaolong; Tan, Bing
Abstract: An inertial shadow Douglas-Rachford splitting algorithm for finding zeros of the sum of monotone operators is proposed in Hilbert spaces. Moreover, a three-operator splitting algorithm for solving a class of monotone inclusion problems is also concerned. The weak convergence of the algorithms is investigated under mild assumptions. Some numerical experiments are implemented to illustrate our main convergence results.